PERANAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM UPAYA MENUNTASKAN WAJIB BELAJAR 9 TAHUN DI MTS NW TEROS TAHUN ANGGARAN 2019/2020 - Sigit Wahyudi (CENDEKIA: Jurnal Studi Keislaman, 2021)
This study discusses the role of School Operational Assistance (BOS) funds in an effort to complete the 9-year compulsory education at MTs NW Teros. BOS is a government program which is basically to provide funding for non-personnel operating costs for basic education units as implementing compulsory education programs. Funds from the central government are distributed through local governments to equivalent SD/MI and SMP/MTs through school accounts to assist school operational activities in the context of completing the nine-year compulsory education of basic education. While the Nine-Year Compulsory Education Program is a development of the Six-Year Compulsory Education Program initiated by the Ministry of National Education (now the Ministry of National Education) in 1984. Through Presidential Instruction No. 1 of 1994, the Six-Year Compulsory Education Program was upgraded to the Nine-Year Compulsory Education Program in primary and junior secondary education. The type of research used in this study is a qualitative approach with a descriptive type of research. Research that uses data mining in the form of words, sentences, and pictures. The various data were obtained from respondents who were then given an interpretation so that the findings were obtained. It can be concluded that the implementation of the School Operational Assistance fund in an effort to complete the 9-year compulsory education at MTS NW Teros has been carried out effectively. The school has specifically formed a BOS Management Team to manage the use of BOS funds. So that from year to year the implementation of BOS at MTS NW Teros has been well patterned and implemented according to the planning and implementation.